Back Cover: Silver‐Catalyzed Cross‐Coupling of Propargylic Alcohols with Isocyanides: An Atom‐Economical Synthesis of 2, 3‐Allenamides (Chem. Eur. J. 8/2014). Issue 8 (17th February 2014) - Liu, Jianquan; Liu, Zhenhua; Wu, Nannan; Liao, Peiqiu; Bi, Xihe
<x xml:space="preserve">Abstract</x> Cross‐coupling between propargylic alcohols and isocyanides, by means of silver catalysis, has been developed. This reaction is atom and step efficient and is applicable to a broad scope of substrates, allowing the synthesis of a range of synthetically valuable 2, 3‐allenamides in moderate to excellent yields. Further details can be found in the Communication by X. Bi and co‐workers on page 2154 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>